2023
DOI: 10.3389/fpubh.2023.1144420
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of affect, emotion regulation, psychological capital, and resilience among Chinese males during the late stage of the COVID-19 pandemic

Abstract: BackgroundPrevious studies have confirmed that both affect and emotion regulation strategies are closely associated with psychological capital (PsyCap) and resilience. These factors are assumed to buffer the effect of the COVID-19 pandemic on mental health, especially among males. However, these interactions have not been closely examined to date. To fill this gap, this paper explores the dimension-level relationships of these psychological constructs among Chinese males during the late stage of the COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Furthermore, the COVID-19 pandemic has accentuated the importance of psychological resilience and a sense of meaning in life. Studies by Guo et al (2023) and Zeng et al (2022) found that these factors were pivotal in helping individuals navigate the psychological challenges posed by the pandemic. The findings of this study contribute to this body of knowledge by showing that both meaning in life and emotional resilience are essential components of mental toughness, particularly in stressful times (Guo et al, 2023;Zeng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the COVID-19 pandemic has accentuated the importance of psychological resilience and a sense of meaning in life. Studies by Guo et al (2023) and Zeng et al (2022) found that these factors were pivotal in helping individuals navigate the psychological challenges posed by the pandemic. The findings of this study contribute to this body of knowledge by showing that both meaning in life and emotional resilience are essential components of mental toughness, particularly in stressful times (Guo et al, 2023;Zeng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Responses are rated on a 5-point Likert scale from 0 (not true at all) to 4 (true nearly all the time), with higher scores indicating greater resilience. The CD-RISC has been validated in numerous studies and has shown high reliability and validity across different populations, making it a reliable tool for assessing emotional resilience (Afek et al, 2021;Darbani & Parsakia, 2023;Eryilmaz et al, 2023;Guo et al, 2023; Han E-ISSN: 3041-8542 & Wang, 2022; İme & Ümmet, 2022;Li, 2023;Liu et al, 2018;Sugawara et al, 2021).…”
Section: Emotional Resiliencementioning
confidence: 99%
See 2 more Smart Citations